Manajemen Stres Menghadapi Covid-19 dalam Pendidikan Islam - Iin Setyani (LPPM IAINU Kebumen, 2021)
The corona covid-19 virus phenomenon is very shocking the world. Almost all people in the world experience uncertainty and many receive information from social media whose truth is uncertain. This has unwittingly caused panic for some people. The number of hoax news that caused panic and the appeal for social distancing by the government without any proper counseling to the community, which resulted in panic. Not only this it also affects the mental health of a person to unwittingly cause stress. The purpose of this study is to find out how to manage stress in dealing with covid-19 in the perspective of Islamic education. The research approach used is a form of research obtained from the literature in the field of Islamic education and stress management. Data collection techniques by searching related literature both online and offline. Data analysis techniques using data analysis techniques from related literature. The results of research conducted are stress management to deal with covid-19 in Islamic education is to think positively, avoid hoax news, avoid excessive panic, pray and worship Allah, and always pray to Allah.